2022
DOI: 10.1111/sdi.13078
|View full text |Cite
|
Sign up to set email alerts
|

Research hotspots and emerging trends of automated peritoneal dialysis: A bibliometric analysis from 2000 to 2020

Abstract: Background The implementation of automated peritoneal dialysis (APD) has considerably increased in many countries. We conducted a bibliometric analysis to evaluate the accumulating studies on APD in the last two decades quantitatively and qualitatively. Methods Publications regarding APD research between 2000 and 2020 were retrieved from the Web of Science Core Collection database by using the index term “automated peritoneal dialysis.” CiteSpace, VOSviewer, and an online platform were employed to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…APD has become the prevalent mode of peritoneal dialysis in most high-income countries. 12 , 13 Previously studies showed that factors such as educational background, occupation, dialysis duration, knowledge of APD, and family support may affect that influence patients’ choosing APD. 5 In this study, we performed a cross-sectional questionnaire-based study to investigate the factors that affect the patients’ choice for APD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…APD has become the prevalent mode of peritoneal dialysis in most high-income countries. 12 , 13 Previously studies showed that factors such as educational background, occupation, dialysis duration, knowledge of APD, and family support may affect that influence patients’ choosing APD. 5 In this study, we performed a cross-sectional questionnaire-based study to investigate the factors that affect the patients’ choice for APD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the most highly cited articles in a field provides insights into key areas and research trends. While bibliometric analyses have been conducted in nephrology on topics such as hemodialysis, automatic peritoneal dialysis, diabetic nephropathy, renal fibrosis, and the relationship between lifestyle changes and CKD, [7][8][9][10] to date, no bibliometric analysis specifically focusing on CKD-MBD articles has been performed. Therefore, this study aims to conduct a comprehensive bibliometric analysis of the top-cited articles on CKD-MBD, providing valuable insights and establishing a foundation for future research.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of automated peritoneal dialysis (APD) which was originally reserved for patients with high transport status has increased over recent years, paralleled by a substantial growth of accumulating studies on APD [1]. Due to its lifestyle benefits, wider range of prescription options, and the availability of convenient automated machines, APD has become a desirable peritoneal dialysis (PD) modality for individuals with other transport characteristics.…”
Section: Introductionmentioning
confidence: 99%